Distinguishing Coronavirus Disease 2019 Patients From General Surgery Emergency Patients With the CIAAD Scale: Development and Validation of a Prediction Model Based on 822 Cases in China - Zhao, Bangbo; Wei, Yingxin; Sun, Wenwu; Qin, Cheng; Zhou, Xingtong; Wang, Zihao; Li, Tianhao; Cao, Hongtao; Wang, Yujun; Wang, Weibin (Frontiers in Medicine, 2021)
Background: In the epidemic, surgeons cannot distinguish infectious acute abdomen patients suspected coronavirus disease 2019 (COVID-19) immediately by current widely applied methods such as double nucleic acid detection. We aimed to develop and validate a prediction model, presented as nomogram and scale, to distinguish infectious acute abdomen patients suspected COVID-19 more effectively and efficiently. Methods: A total of 584 COVID-19 patients and 238 infectious acute abdomen patients were enrolled. The least absolute shrinkage and selection operator (LASSO) regression and multivariable logistic regression analyses were conducted to develop the prediction model. The performance of the nomogram was evaluated by calibration curves, Receiver Operating Characteristic (ROC) curves, decision curve analysis (DCA) and clinical impact curves in the training and validation cohorts. A simplified screening scale and management algorithm were generated based on the nomogram. Results: Five potential COVID-19 prediction variables, fever, chest CT, WBC, CRP and PCT, were selected, which were all independent predictors in multivariable logistic regression analysis, and the nomogram, named the COVID-19 Infectious Acute Abdomen Distinguishment (CIAAD) nomogram, was generated. The CIAAD nomogram showed good discrimination and calibration, and it was validated in the validation cohort. Decision curve analysis revealed that the CIAAD nomogram was clinically useful. The nomogram was further simplified as the CIAAD scale. Conclusion: We established an easy and effective screening model and scale for surgeons in the emergency department to use to distinguish COVID-19 patients. The algorithm based on the CIAAD scale will help surgeons more efficiently manage infectious acute abdomen patients suspected of having COVID-19.